MEMBEKALKAN PENGETAHUAN PROSEDURAL DAN SIKAP ILMIAH KEPADA SISWA SMA MELALUI PEMBELAJARAN VIRTUAL LABORATORY - Kurratul Aini; Megawati Megawati; Nofa Rojayanti (Jurnal BIOEDUIN, 2021)
Practicum using a virtual laboratory is an alternative practicum activity for students in schools that do not have laboratory facilities so that the learning objectives can be achieved. The aim of this study is to know influence virtual laboratory for procedural knowledge and scientific attitudes of students on matter of excretion at class XI SMA Negeri 4 Palembang. Method is an experimental research with The One Group Pretest-Posttest Design. The sampling technique was purposive sampling, with a total sample of 169 students of class XI IPA. Data collection techniques for procedural knowledge using pretest and posttest and, questionnaires of scientific attitude. The results obtained an average score of pretest 8.08 and posttest 16.33. Increased procedural knowledge is shown by the n-gain value of 0.68 in the medium category. Based on the results of the hypothesis test obtained a significance value of 0.000 <0.05, so that H1 is accepted, which means a significant difference between the average pretest and posttest. For scientific attitudes, average percentage of 82.27% with a good category. It can be concluded that there is an influence of virtual laboratory on procedural knowledge and scientific attitudes of students.